Gestational TSH and FT4 Reference Intervals in Chinese Women: A Systematic Review and Meta-Analysis - Gao, Xiaotong; Li, Yongze; Li, Jiashu; Liu, Aihua; Sun, Wei; Teng, Weiping; Shan, Zhongyan (Frontiers in Endocrinology, 2018)
Background: Serum thyroid-stimulating hormone (TSH) and free thyroxine (FT4) change dynamically during pregnancy. Various regions, populations, and manufacturer's methodologies can affect the reference intervals for thyroid function tests. The 2017 guidelines of the American Thyroid Association (ATA) recommended 4.0 mU/L as the cut-off point for the upper limit of serum TSH in early pregnancy. A systematic review is called for to establish practical, gestational-specific TSH and FT4 reference intervals for pregnant Chinese women and to explore whether the criteria are suitable for China. Methods: English and Chinese articles published from inception to Aug 2017 were searched in the PubMed, EMBASE, and SCIE English-language databases and the CNKI, WanFang, and CQVIP Chinese databases. The relative descent or ascent rates of serum TSH and FT4 were calculated, after which Comprehensive Meta-Analysis V2.0 software was used to analyze the data. Results: Eleven studies (6 in English and 5 in Chinese), five kits and 11,629 Chinese women from nine cities were considered in this meta-analysis. Compared with the reference ranges provided by manufacturers, serum TSH decreased in the first trimester, with the upper limit declining by 21.7% (5.0% - 36.6%), to a value close to 4.0 mU/L, and the lower limit declining by 85.7% (73.5% - 97.1%). It continued decreasing in the second trimester, with the upper limit declining by 24.0% (6.4% - 40.9%) and the lower limit declining by 40.7% (9.0% - 85.7%). For FT4, the upper limit fluctuated slightly, and the lower limit increased by 6.8% (1.0% - 14.6%) in the first trimester. Serum FT4 dropped gradually, with the upper limit declining by 21.8% (2.5% - 31.8%) and the lower limit declining by 12.7% (2.6% - 19.6%) in the second trimester. During the third trimester, the upper limit decreased by 25.1% (12.7% - 35.0%), while the lower limit decreased by 20.9% (14.8% - 27.3%). Conclusions: Various regions, kits and test methods affect the gestational TSH and FT4 levels. The non-pregnant serum TSH upper limit minus 22% is very close to 4.0 mU/L, which can be used as a sub-optimal approach to represent the cut-off value for pregnant Chinese women during early pregnancy.